2014
DOI: 10.1590/s0102-86502014000800008
|View full text |Cite
|
Sign up to set email alerts
|

Copaiba oil effect under different pathways in mice subjected to sepsis

Abstract: PURPOSE:To evaluate the effects of copaiba oil administered by different routes on survival of mices subjected to cecal ligation and puncture. METHODS:Thirty two mice were distributed into four study groups (N=8): Sham group: normal standard animals; Control group: submitted a cecal ligation and puncture (CLP); Gavage group: submitted a CLP, and treat with copaiba oil by gavage; and Subcutaneous group: submitted a CLP, and treat with copaiba oil by subcutaneous injection. After the death of the histological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In the present study, we compared the effects 0.9% saline, modified coconut water (Na 3%) and water coconut 3% + Na + simvastatin, and normal coconut water on serum cytokines, biochemical and white blood cell count in rodent model with hemorrhagic shock and abdominal sepsis. Experimental models of sepsis and hemorrhagic shock has often been employed in other estudies [30][31][32] . In the present study, we found that treatment of rats with sepsis and shock with coconut water modified with sodium 3% + simvastatin reduced serum cytokines, biochemical parameters and peripheral leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared the effects 0.9% saline, modified coconut water (Na 3%) and water coconut 3% + Na + simvastatin, and normal coconut water on serum cytokines, biochemical and white blood cell count in rodent model with hemorrhagic shock and abdominal sepsis. Experimental models of sepsis and hemorrhagic shock has often been employed in other estudies [30][31][32] . In the present study, we found that treatment of rats with sepsis and shock with coconut water modified with sodium 3% + simvastatin reduced serum cytokines, biochemical parameters and peripheral leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The CLP model of sepsis has been a mainstay of basic sepsis research; Some medicinal plants have been tested in that model [9,[18][19][20][21], most with encouraging result; however, the aloe has been used therapeutically for many centuries and has the advantage of clinical studies demonstrating its safety and effectiveness in several diseases [22][23][24], facilitating the translation. However, more studies are necessary to assess variables of drug administration such as: the best routes of administration (oral, subcutaneous, intraperitoneal or intravenous) and dose and frequency of administration for better results [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are necessary to assess variables of drug administration such as: the best routes of administration (oral, subcutaneous, intraperitoneal or intravenous) and dose and frequency of administration for better results [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…-Sham Group (GS): The animals were used as normal standard for biochemical and histological analysis; the animals underwent the same surgical techniques, but without the performance of CLP; -Sepsis Group (GSep): Animals were only realized the cecal ligation and puncture (CLP) [8]; -Veronica Group (GV): Administered Veronica officinalis extract (10ml/kg/day) once daily by gavage for seven days [9], without the performance of cecal ligation and puncture (CLP); -Sepsis-Veronica Group (GSep-V): Administered Veronica officinalis extract (10ml/kg/day) once daily by gavage from the first until the seventh day of the CLP. The animals were anesthetized with ketamine hydrochloride (100 mg/Kg) and xylazine hydrochloride (10 mg/Kg), intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%